Development of a new hyper crosslinked resin based on polyamine-isocyanurate for the efficient removal of endocrine disruptor bisphenol-A from water (2023)
Bisphenol A (BPA) is a diphenylmethane derivative often used as a building block of polycarbonate in the production of plastic and plastic additives. Different sectors of the chemical industry release daily high concentrations of BPA in treatment plants, leading to polluting the environment. Due to chemical characteristics, BPA is considered highly toxic to animals and humans health. Adsorption is considered one of the promising techniques for the removal of BPA from water. In this study, we report the synthesis of a new polyamine-isocyanurate-based hyper crosslinked resin (ICYAN-PA) for the adsorptive removal of BPA from aqueous solution. The porous resin showed good thermal stability with a surface marked by smooth porous layers covered by particles of different sizes. The resin exhibited optimum removal of BPA at pH 5, with an adsorption capacity of 260 mg g−1. The isothermal studies suggested that adsorption was favored with increasing temperature (318 K). The Koble-Corrigan model was more adequate to represent the isothermal data. Moreover, the adsorption process was favorable, spontaneous, and endothermic (ΔH0 = 50.9 kJ mol−1). Furthermore, the magnitude of ΔH° was compatible with physical adsorption. The kinetic profiles indicated that the adsorption equilibrium was attained in <180 min of contact time, and the pseudo-first order model best represented the kinetic data. Given the relatively fast kinetics and high thermal stability (Td < 220 °C), ICYAN-PA holds a promise in the decontamination of effluents containing BPA.